Mediation of ACTH and prolactin responses to 5-HTP by 5-HT2 receptors. - Gartside, SE; Cowen, P (1990)
Serotonin has a facilitatory role in the role of prolactin and adrenocorticotropin (ACTH) secretion. The serotonin precursor 5-hydroxy-L-tryptophan (5-HTP) dose dependently (30-100 mg/kg i.p.) increased plasma prolactin and ACTH in the male rat. Prolactin and ACTH responses to 5-HTP (100 mg/kg) were attenuated by pretreatment with the non-selective 5-HT receptor antagonist, metergoline (0.5 mg/kg), and by the selective 5-HT2 receptor antagonists, ritanserin (0.4 mg/kg), ketanserin (2.5 mg/kg), ICI (5.0 mg/kg) and spiperone (1.0 mg/kg). The 5-HT1 receptor antagonists, propranolol (40 mg/kg) and pindolol (4.0 mg/kg), failed to antagonize the prolactin and ACTH responses to 5-HTP (100 mg/kg), as did the selective 5-HT3 receptor antagonist, BRL 43694 (1.0 mg/kg). The results suggest that the prolactin and ACTH responses to 5-HTP in the male rat are mediated by 5-HT2 receptors.